Investigation of the ability to manipulate light polarization properties in a liquid crystal cell filled with ferronematic material through electric and magnetic fields - Korec-Kosturek, Joanna; Niewczas, Michał; Dziaduszek, Jerzy; Kula, Przemysław; Zbonikowski, Rafał; Paczesny, Jan; Stasiewicz, Karol A. (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
This research paper investigates the integration of liquid crystals doped with magnetic nanoparticles into optical fiber systems to examine changes in light propagation parameters, with emphasis on polarization. The study leverages the unique anisotropic properties of LCs and the tunable characteristics introduced by MNPs for novel sensor applications. Various concentrations of MNPs (from 0.1 to 0.5 wt%) are introduced into the 6CHBT liquid crystal matrix, and the effects of electric and magnetic fields on polarization parameters such as azimuth and ellipticity are analyzed. Results show significant exponential changes in these parameters occurring at a doping concentration of 0.1 wt% and stabilizing above 120 V, while higher concentrations yield smaller linear changes. The polarization direction shifts from left- to right-handed with increasing concentrations of MNPs, and applying a magnetic field intensifies these effects. Overall, this paper demonstrates the potential of the developed system for applications such as tunable optical filters and sensors for temperature, magnetic, and electric fields.